KONSEP KEDATUAN DALAM SISTEM KERAJAAN LUWU PERSPEKTIF SIYASAH SYAR’IYYAH - Indra, Muh. Indra Kaesar B; Hisbullah; Mustafa, Adriana (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This research aims to examine the position of the kedatuan within the governmental system of the Luwu Kingdom, the relationship between the kedatuan and the institutions of the Luwu Kingdom, and the perspective of Siyasah Syar’iyyah on the concept of Luwu Kingdom governance. This study is classified as library research using a normative approach, with primary data derived from previous scholarly studies (journals) on the Luwu Kingdom and the Qur’an, supported by secondary data in the form of relevant books and scientific articles. Data were collected through identification, selection, and editing, and analyzed qualitatively. The findings indicate that the kedatuan occupies the highest leadership position in the Luwu Kingdom, where the ruler is referred to as Datu rather than king. Initially, the Luwu Kingdom applied an absolute monarchy system, which later developed into a constitutional monarchy in line with the advancement of knowledge. The relationship between the kedatuan and the kingdom’s institutions is constitutional, reflected in the division of powers (trias politica) among Ade’ Sappulo Dua, Ade’ Asera, and To Maraja Pakkatenni. Ade’ Sappulo Dua is responsible for appointing the Datu and enacting laws, Ade’ Asera supervises governmental administration, and To Maraja Pakkatenni carries out the daily duties of the Datu. From the perspective of Siyasah Syar’iyyah, the Luwu Kingdom’s system of governance after Islamization aligns with Islamic principles, whereas the pre-Islamization system does not conform to universal Islamic teachings